ANALISIS POTENSI PENDAPATAN ASLI DAERAH DI KABUPATEN FAKFAK PROVINSI PAPUA BARAT - Gewab, Novan; Rumbia, Wali Aya; Ahmad, Ahmad (Jurnal Ekonomi Pembangunan (JEP) UHO, 2023)
The purpose of this study is to determine the potential of local revenue in Fakfak Regency, West Papua Province. Using a descriptive analysis method, which is to provide an overview of the Potential of Regional Original Income. The results of this study indicate that: (1) the realization of PAD revenue fluctuated initially there was an increase but in 2019 there was a decrease due to the Covid 19 condition which until now has not been completed and then there was an increase; (2) The potential for local revenue in Fakfak Regency, West Papua Province comes from Regional Revenue, Regional Original Revenue, Balancing Funds, Other Legitimate Regional Income, Regional Expenditures, Indirect Expenditures, Direct Expenditures and Surplus/Deficit. Potential Local Original Income in Fakfak Regency in addition to taxes and levies originating from PAD, other potentials are Agricultural Potential, Plantation Potential, Livestock Potential, Fishery Potential, Forestry Potential, Mining Potential and Tourism Potential.